PENERAPAN EDMODO PADA PEMBERIAN TES FORMATIF MAHASISWA PENDIDIKAN PROFESI GURU MATEMATIKA - Reni Dwi Susanti (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This research aims to describe the application of formative tests on edmodo granting the student mathematics teacher education profession. This type of research is descriptive with qualitative approach. Data retrieval by way of observation, online tests and student response. The results of the research shows that with the application of the test for granting edmodo formative student PPG mathematics education is running very well and can be applied to the grant of formative tests. With Edmodo can easily see the results obtained by students, besides that with Edmodo can easily see the material that many students answered incorrectly and the settings for execution time can also be set. So that, with this time arrangement, the students will be able to manage the process of the question well. Edmodo also provides facilities to be able to randomize answers with questions in appearance, so that with the existence of the facility there is a possibility that between one student and another student gets the same problem but with a different number. The facility can also minimize students from working together. The implementation is also supported by several student responses. The results of student responses in the application of Edmodo for the provision of this formative test are very good.